Targeted Killing from the Perspective of International Law and US Domestic Law: A Case Study of the Assassination of Major General Soleimani - Sattar Azizi (پژوهش تطبیقی حقوق اسلام و غرب, 2020)
The assassination of Martyr Qassem Soleimani, by order of the President of the United States, raised the issue of the legality of the assassination in terms of international law and the US domestic legal system in legal circles. The Israeli and US governments have coined the concept of "Targeted Killing" with the pretext of combating terrorism and have assassinated those who they believed to be terrorists and in fact opposed them. In this article, through a comparative study, the institution of targeted killing is examined from the standpoint of international law and US domestic law. In US domestic law, assassination is prohibited by Executive Order 12333. In the recent two decades, targeted killings of al-Qaeda and Taliban members have been carried out under specific congressional rules, and the assassination of General Soleimani has not been authorized by Congress to use force against Iran. Furthermore, owing to the fact that General Soleimani was one of the military commanders of the Iranian government and there is no armed conflict between the governments of Iran and the United States, this targeted assassination is contrary to international law, including international human rights law and international humanitarian law.